2021
DOI: 10.3389/fnana.2021.674649
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin-3 Innervation From the Nucleus Incertus to the Parahippocampal Cortex of the Rat

Abstract: Spatial learning and memory processes depend on anatomical and functional interactions between the hippocampus and the entorhinal cortex. A key neurophysiological component of these processes is hippocampal theta rhythm, which can be driven from subcortical areas including the pontine nucleus incertus (NI). The NI contains the largest population of neurons that produce and presumably release the neuropeptide, relaxin-3, which acts via the Gi/o-protein-coupled receptor, relaxin-family peptide 3 receptor (RXFP3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
0
7
0
1
Order By: Relevance
“…Numerous earlier anatomical studies have characterized the connectivity and neurophysiological activity of the NI in rat and mouse brain, including the strong projections to the SHS system, and to multiple cortical and limbic areas involved in emotional cognition [14,17,18, 21], while others have characterized the nature of the transmitters, neuropeptides, and receptors expressed by different populations of NI neurons in these species [14][15][16][17][18][19][20][21][22], which provide an insight to the likely functional role of the NI in the human brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous earlier anatomical studies have characterized the connectivity and neurophysiological activity of the NI in rat and mouse brain, including the strong projections to the SHS system, and to multiple cortical and limbic areas involved in emotional cognition [14,17,18, 21], while others have characterized the nature of the transmitters, neuropeptides, and receptors expressed by different populations of NI neurons in these species [14][15][16][17][18][19][20][21][22], which provide an insight to the likely functional role of the NI in the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, many decades later, a large majority of neurons in the rat NI or nucleus O [12] was shown to express the inhibitory neurotransmitter, γ-aminobutyric acid (GABA), as reflected by staining against the GABA-synthesizing enzyme, GAD, and in situ hybridization (ISH) for vGAT1 mRNA [13,14]. Since then, the neuroanatomy of the NI and its connections throughout the brain has been systematically mapped using various histological methods in rats [14][15][16][17][18][19], mice [20][21][22][23][24], zebrafish [25], and in non-human primate [26], but not in humans.…”
Section: Introductionmentioning
confidence: 99%
“…206,214,220,[266][267][268][269][270][271][272][273][274][275][276][277] In earlier studies, and more recently, comprehensive investigations have characterized receptors for various transmitters/peptides that are present on relaxin-3 neurons within the nucleus incertus [278][279][280][281] and further details of the anatomical networks utilizing relaxin-3/RXFP3 signaling in rat and mouse, 282 including those in the medial septum, 283 hippocampus, and piriform cortex. 284,285 A further aspect of relaxin-3/RXFP3 signaling recently reported was an association with the signaling of cellular aging. Using in vivo co-regulation analyses Maudsley and colleagues 286,287 observed that It should be noted that the structural similarities of relaxin-3 and relaxin, allow relaxin-3 to be tested pharmacologically as a likely RXFP1 agonist in various models, 288 and several reports describe its actions under these conditions.…”
Section: Recent Advances and Current Anatomical And Functional Knowledgementioning
confidence: 97%
“…In earlier studies, and more recently, comprehensive investigations have characterized receptors for various transmitters/peptides that are present on relaxin‐3 neurons within the nucleus incertus 278–281 and further details of the anatomical networks utilizing relaxin‐3/RXFP3 signaling in rat and mouse, 282 including those in the medial septum, 283 hippocampus, and piriform cortex 284,285 …”
Section: Insulin‐like (Relaxin)‐family Peptide and Receptor Systemsmentioning
confidence: 99%
“…Anxiety, along with associated disorders such as post-traumatic stress disorder (PTSD), have in recent years been strongly associated with premature aging conditions [150][151][152][153]. With respect to the impact of RXFP3 upon anxiety-related disorders, it has been shown that specific central stimulation generates an anxiolytic effect in model organisms [154].…”
Section: Anxiety and Post-traumatic Stress Disordermentioning
confidence: 99%